2016
DOI: 10.15171/jlms.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

Periosteal Releasing Incision With Diode Laser in Guided Bone Regeneration Procedure: A Case Series

Abstract: Introduction: Periosteal releasing incision (PRI) is nearly always essential to advance the flap sufficiently for a tension-free flap closure in bone augmentation procedures. However, hematoma, swelling, and pain are recognized as the main consequences of PRI with scalpel. The aim of this case series was to investigate the effectiveness of laser-assisted PRI in guided bone regeneration (GBR) procedure. In addition, postoperative hematoma, swelling, and pain and implant success were assessed. Methods: Seventeen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Out of the 23 studies (Table 1), there were 11 randomised controlled clinical trials [21-24, 26, 29-32, 36, 37, 39], one prospective cohort study [34,40], three retrospective cohort studies [18,20,33], and eight case series [16,17,19,25,27,28,35,38,[41][42][43], of which two research groups independently published two follow-up papers on the same study cohort [21,22,27,28], and they have been collectively grouped under one study name for this analysis. The follow-up period after ridge augmentation or implant placement was reported in all studies except two [16,35], and it ranged from 3.1 months to 10 years.…”
Section: Study Design and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 23 studies (Table 1), there were 11 randomised controlled clinical trials [21-24, 26, 29-32, 36, 37, 39], one prospective cohort study [34,40], three retrospective cohort studies [18,20,33], and eight case series [16,17,19,25,27,28,35,38,[41][42][43], of which two research groups independently published two follow-up papers on the same study cohort [21,22,27,28], and they have been collectively grouped under one study name for this analysis. The follow-up period after ridge augmentation or implant placement was reported in all studies except two [16,35], and it ranged from 3.1 months to 10 years.…”
Section: Study Design and Characteristicsmentioning
confidence: 99%
“…The follow-up period after ridge augmentation or implant placement was reported in all studies except two [16,35], and it ranged from 3.1 months to 10 years. Two studies excluded smokers [30,38], 14 studies reported periodontal status of subjects [16-18, 21-23, 25-30, 35, 36, 40-43], and excluded subjects with untreated periodontal disease, or with a full mouth plaque score and full mouth bleeding score of more than 25%.…”
Section: Study Design and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent these complications, tension-free primary closure is a prerequisite for successful GBR surgery 4 . A periosteal releasing incision is a predictable and easy way to advance the flap when the soft tissue is insufficient to achieve complete coverage 5 , 6 . However, as the extent of release increases, the degree of hematoma, swelling, and pain also increase which has a significant effect on the quality of life of patients after surgery and can lead to surgical results that are not ideal 6 .…”
Section: Introductionmentioning
confidence: 99%